Tripartite Entanglement for Qubits and Qudit in Double Photoionization of Xenon Atom - Chakraborty, Minakshi; Sen, Sandip (Transactions on Engineering and Computing Sciences, 2019)
Quantum entanglement holds the key to an information processing revolution. In this article, we study the entanglement properties of tripartite states of two electronic qubits and ionic qudit,without observing spin orbit interaction (SOI), produced by single-step double photoionization from Xeon atom following the absorption of a single photon. The dimension of the Hilbert space of the qudit depends upon the electronic state of the residual photoion Xe2+. In absence of SOI, Russel-Salunders coupling (L-S coupling) is applicable. As the estimations of entanglement, we consider Peres-Horodecki condition and negativity. In case of L-S coupling, all the properties of a qubit-qudit system can be predicted merely with the knowledge of the spins of the target atom, the residual photoion, emitted electrons and state of polarization of the incident photons.